The Relationship Of Parent’Attention with The Results of Science Learning Grade VIII Students of SMP Negeri 15 Padang - Riza Novita; Zulyusri Zulyusri; Siska Aulia Farma; Ristiono Ristiono (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The purpose of this research is to determine the relationship of parents' attention with the science learning Grade VIII students of SMP Negeri 15 Padang. The population in this research amounted to 178 students with a total sample of 60 students, taken by random sampling technique. Data collection was obtained using questionnaires and documentation. Data analysis techniques were used using descriptive and correlation analysis techniques. The calculation result of r count> r table is 0.257> 0.250 which means that there is a positive relationship between the attention of parents and the results of natural science learning Students of Grade VIII of SMP Negeri 15 Padang.